2014
DOI: 10.1111/ina.12099
|View full text |Cite
|
Sign up to set email alerts
|

Personal inhalation exposure to polycyclic aromatic hydrocarbons in urban and rural residents in a typical northern city in China

Abstract: Personal inhalation exposure samples were collected and analyzed for polycyclic aromatic hydrocarbons (PAHs) for 126 selected volunteers during heating and non-heating seasons in a typical northern Chinese city, Taiyuan. Measured personal PAH exposure levels for the urban residents in the heating and non-heating seasons were 690 (540-1051) and 404 (266-544) ng/m(3) , respectively, while, for the rural residents, they were 770 (504-1071) and 312 (201-412) ng/m(3) , respectively. Thus, rural residents are expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…It is interesting to note that globally, the ILCR due to the inhalation exposure of ambient PAHs was estimated at 3.1×10 −5 (Shen et al, 2014), and in some cities with severe ambient pollution reported ILCR due to the PAH inhalation exposure were 3.36×10 −5 and 2.39×10 −5 for the rural and the urban residents in Taiyuan, Shanxi province (Duan et al, 2014). The ILCR due to the PAH inhalation exposure in Beijing was 1.83×10 −5 (1.30×10 −5 −4.48×10 −5 as interquartile range) and 2.40 ×10 −5 (9.92×10 −6 −3.46×10 −5 ) for the male and the female, respectively (Yu et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that globally, the ILCR due to the inhalation exposure of ambient PAHs was estimated at 3.1×10 −5 (Shen et al, 2014), and in some cities with severe ambient pollution reported ILCR due to the PAH inhalation exposure were 3.36×10 −5 and 2.39×10 −5 for the rural and the urban residents in Taiyuan, Shanxi province (Duan et al, 2014). The ILCR due to the PAH inhalation exposure in Beijing was 1.83×10 −5 (1.30×10 −5 −4.48×10 −5 as interquartile range) and 2.40 ×10 −5 (9.92×10 −6 −3.46×10 −5 ) for the male and the female, respectively (Yu et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Cardiovascular disease has been shown to account for higher mortality rates than respiratory illness in China (He et al 2005). In an effort to curb air pollution, several large cities in China have recently banned household coal burning; however, an estimated 10% of ambient PM 2.5 (PM with diameter ≤ 2.5 μm) derived from cooking with coal in 2010 (Chafe et al 2014), and an estimated 38% of the population still used coal for cooking in 2009–2010 (Duan et al 2014) in rural parts of China. Evidence from this study suggests that household coal use could lead to excess deaths years after last exposure among women in Shanghai, although for cardiovascular disease mortality we observed a notable decreasing trend in risk as the time since last use of coal increased.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most surveys have not reported HFU for space heating. It has been recognized that large amounts of fuel are consumed for household heating during the cold season in most developing countries, and this kind of fuel consumption leads to serious indoor and outdoor pollution [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%